An invasive seagrass drives its own success in two invaded seas by both negatively affecting native seagrasses and benefiting from those costs - Chiquillo, Kelcie L.; Barber, Paul H.; Vasquez Christodoulou, Marlen; Cruz-Rivera, Edwin; Willette, Demian A.; Winters, Gidon; Fong, Peggy (My University, 2023)
The nature and strength of interactions between native and invasive species can determine invasion success. Species interactions can drive, prevent or facilitate invasion, making understanding the nature and outcome of these interactions critical. We conducted mesocosm experiments to test the outcome of interactions between Halophila stipulacea, a seagrass that invaded the Mediterranean and Caribbean Seas, and native seagrasses (Cymodocea nodosa and Syringodium filiforme, respectively) to elucidate mechanisms explaining the successful invasions. Mesocosms contained intact cores with species grown either mixed or alone. Overall, in both locations, there was a pattern of the invasive growing faster with the native than when alone, while also negatively affecting the native, with similar patterns for shoot density, aboveground and belowground biomass. In the Caribbean, H. stipulacea increased by 5.6 ± 1.0 SE shoots in 6 weeks when grown with the native while, when alone, there was a net loss of −0.8 ± 1.6 SE shoots. The opposite pattern occurred for S. filiforme, although these differences were not significant. While the pattern in the Mediterranean was the same as the Caribbean, with the invasive grown with the native increasing shoots more than when it grew alone, these differences for shoots were not significant. However, when measured as aboveground biomass, H. stipulacea had negative effects on the native C. nodosa. Our results suggest that a seagrass that invaded two seas may drive its own success by both negatively affecting native seagrasses and benefiting from that negative interaction. This is a novel example of a native seagrass species facilitating the success of an invasive at its own cost, providing one possible mechanism for the widespread success of this invasive species.
Keywords: Facilitation; Invasion ecology; Negative interactions; Plant invasion; Seagrasses; Species interactions